2012
DOI: 10.4103/2230-973x.96925
|View full text |Cite
|
Sign up to set email alerts
|

Dissolution enhancement of glimepiride using modified gum karaya as a carrier

Abstract: Objective:The aim of present investigation is to enhance in vitro dissolution of poorly soluble drug glimepiride by preparing solid dispersions using modified gum karaya.Materials and Methods:Solid dispersions of drug were prepared by solvent evaporation method using modified gum karaya as carrier. Four batches of solid dispersion (SD1, SD4, SD9, and SD14) and physical mixture (PM1, PM4, PM9, and PM14) were prepared and characterized by differential scanning colorimetry (DSC), Fourier transform infrared (FTIR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…FTIR of pure GMD showed characteristic sharp peaks at 3369 cm -1 and 3288 cm -1 due to N-H stretching, 1707 cm -1 and 1674 cm -1 due to carbonyl group, 1345 cm -1 indicating C-N stretching vibration, 1153 cm -1 confirmed S=O stretching vibration [9] as depicted in figure (1A).…”
Section: Physicochemical Compatibilitymentioning
confidence: 91%
See 1 more Smart Citation
“…FTIR of pure GMD showed characteristic sharp peaks at 3369 cm -1 and 3288 cm -1 due to N-H stretching, 1707 cm -1 and 1674 cm -1 due to carbonyl group, 1345 cm -1 indicating C-N stretching vibration, 1153 cm -1 confirmed S=O stretching vibration [9] as depicted in figure (1A).…”
Section: Physicochemical Compatibilitymentioning
confidence: 91%
“…However, GMD as well as with other oral hypoglycemic drugs has shown several adverse and potential side effects related to hypoglycemia with inaccurate dosing. Recently, there is a growing interest to enhance and control the transdermal delivery of GMD using matrix of natural and synthetic materials [6][7][8][9]. The aim of the current study was to develop GMD transdermal patches to control insulin nondependent diabetes (type II).…”
Section: Introductionmentioning
confidence: 99%
“…In the earlier studies conducted on glimepiride 40 to 75% improvement in dissolution rate was observed in case of solid dispersions prepared using PVP k-30 as compared to pure drug whereas solid dispersions prepared using guar gum could release only 30% drug within 10 min. [21,22]. Therefore it can be said that formulating nanosuspensions of glimepiride by simple high shear homogenization method using hydrophilic polymer HPMC E-15 which acts as a steric stabilizer could enhance dissolution rate significantly [23] The increase in dissolution profile of GNS2 may be due to an increase in the stirring times during preparation as compared to their respective nanosuspension formulations, which resulted in smaller particle sizes.…”
Section: In Vitro Dissolution Studies Of Glimepiride Nanosuspensionsmentioning
confidence: 99%
“…[9] Evaluation Characterization of xanthan gum and modified xanthan gum for viscosity and swelling index. [2,10] Viscosity A 0.5% aqueous solution of sample was added to the viscometer, pulled into the upper reservoir by suction and then allowed to drain by gravity back into the lower reservoir. The time that it takes for the liquid to pass between two etched marks, one above and one bellow the upper reservoir, is measured.…”
Section: Fourier Transform Infrared Spectroscopy (Ftir)mentioning
confidence: 99%
“…10 grams of powdered GK was taken in a porcelain bowl and subjected to heating using a sand bath for 2hr at 120 o C. [2,3] Preparation of modified xanthan gum…”
Section: Preparation Of Modified Karaya Gummentioning
confidence: 99%